The QUALITY BY DESIGN APPROACH FOR SIMULTANEOUS DETERMINATION OF FLUTICASONE PROPIONATE AND SALMETEROL XINAFOATE - KULKARNI, PANKAJ N.; JADHAV, C. K.; DODAKE-SUPEKAR, ALAKNANDA M.; GILL, CHARANSINGH H. (International Journal of Applied Pharmaceutics, 2020)
Objective: To develop and validate a novel and simple reverse phase Ultra Performance Liquid Chromatography (UPLC) method for simultaneous determination of Fluticasone Propionate and Salmeterol Xinafoate from pharmaceutical finished product, applying Quality by design (QbD) approach. Methods: The proposed analytical method developed and validated in a linear gradient condition at a flow rate of 0.40 ml/min over Waters ACQUITY BEH Shield RP 18, 2.1*100 mm, 1.7 µm column by maintaining column oven temperature at 30 °C and Sample cooler temperature at 15 °C. Chromatograms monitored and recorded at 215 nm. Results: The proposed method has been validated as per International Conference on Harmonization (ICH) guidelines with respect to system suitability, specificity, precision, linearity, accuracy, range, solution stability and robustness. This method is qualified in all parameters in case of system suitability and specificity; precision observed within the limit of 2.0%, the excellent linear response observed with correlation coefficient (R2) for Salmeterol 0.99999 and Fluticasone Propionate 0.99999, for Accuracy within the limit of 98% to 102%. Conclusion: A selective, suitable and accurate reverse phase UPLC method for simultaneous Determination of Fluticasone Propionate and Salmeterol Xinafoate in the pharmaceutical finished product has been developed and validated successfully.